(untitled) - Pearlson, Keri (Hoboken, N.J., 2010)
Pearlson and Saunders’ Third Edition of Managing and Using Information Systems: A Strategic Approach gives students the insights and knowledge they need to become active participants in information systems decisions. By demonstrating how IT relates to organizational design and business strategy, this title covers the essential concepts of MIS. Within the 4th edition, students will also learn how to recognize opportunities in the work environment and apply current technologies in innovative ways. In a concise, updated format, Pearlson and Saunders provide a strategic approach to Information Systems for a senior/graduate level course or as a supplement for any course using additional cases and readings.
Keywords: Knowledge management,Information technology,Management information systems,Business enterprises,Industrial management,Strategic planning,Kế hoạch chiến lược,Hệ thống quản lý thông tin; Management,Computer networks,Data processing,Data processing,Xử lý dữ liệu